Physical Exercise Promotes Novel Object Recognition Memory in Spontaneously Hypertensive Rats after Ischemic Stroke by Promoting Neural Plasticity in the Entorhinal Cortex - Pan, Xiaona; Jiang, Ting; Zhang, Liying; Zheng, Haiqing; Luo, Jing; Hu, Xiquan (Frontiers in Behavioral Neuroscience, 2017)
Cerebral ischemia leads to memory impairment, and several studies have indicated that physical exercise (PE) has memory-improving effects after ischemia. This study was designed to further explore the specific role of PE in novel object recognition (NOR) memory after stroke and the exact cortical regions in which memory is restored by PE. Spontaneously hypertensive rats (SHR) were subjected to transient middle cerebral artery occlusion (tMCAO) or sham surgery, followed by 26 days of PE starting on day 3 post-tMCAO. Thereafter, infract volumes, neurobehavioral outcomes, and NOR memory were assessed. Immunofluorescence staining and Luxol Fast Blue (LFB) staining were performed in the prefrontal cortex, entorhinal cortex and corpus callosum regions. Western blot analysis was performed to detect expression of Nestin, Bcl-2 and SYN proteins in the entorhinal cortex. After tMCAO, NOR memory impairment was found in SHR. Rats subjected to PE post-tMCAO showed increased discrimination ratio, as well as significant decreases in infarct volumes and modiﬁed neurological severity scores, when compared with tMCAO rats without PE. After stroke, NeuN-positive cell number was drastically reduced in the entorhinal cortex, rather than in the prefrontal cortex. Ischemic stroke had no impact on myelin and phospholipids, and the ratio of SMI-32/MBP in the corpus callosum. PE increased NeuN, Nestin, Ki67, MBP, SYN, PSD-95 and Bcl-2 expression in the entorhinal cortex, while TUNEL and SMI-32 expression was decreased. In conclusion, the NOR memory-improving capacity promoted by PE was closely related to neuronal cell proliferation and synaptic plasticity of the entorhinal cortex.